2022
DOI: 10.3389/fsurg.2022.837545
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Intraoperative Blood Loss and Intraoperative Blood Transfusion on the Short-Term Outcomes and Prognosis of Colorectal Cancer: A Propensity Score Matching Analysis

Abstract: PurposeThe purpose of the current study was to analyze the effect of intraoperative blood loss (IBL) and intraoperative blood transfusion (IBT) on the short-term outcomes and prognosis for patients who underwent primary colorectal cancer (CRC) surgery.MethodsWe retrospectively collected the patients' information from the database of a teaching hospital from January 2011 to January 2020. IBL and IBT were collected and analyzed, and the propensity score matching (PSM) analysis was performed.ResultsA total of 4,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The remaining four studies 21 , 24–26 did not report which types of blood products were transfused. Of the 12 included studies, six studies originated from Asia 16–19 , 25 , 27 , five from Europe 20–23 , 26 , and one from the USA 24 . All studies except one 24 were performed at a single centre.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining four studies 21 , 24–26 did not report which types of blood products were transfused. Of the 12 included studies, six studies originated from Asia 16–19 , 25 , 27 , five from Europe 20–23 , 26 , and one from the USA 24 . All studies except one 24 were performed at a single centre.…”
Section: Resultsmentioning
confidence: 99%
“…Intraoperative blood loss was also within an acceptable range and was even lower (80.5 ml) in the last two cases. Previous studies have shown that surgical pro ciency can affect intraoperative blood loss, which in turn in uences postoperative morbidity and recovery [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of CRC is higher in the elderly ( 27 , 28 ). Advanced age is an important risk factor for postoperative mortality and the elderly had poor performance status, recovery ability and comorbid diseases.…”
Section: Discussionmentioning
confidence: 99%